Disparity in pre-emptive end-of-life conversation experience caused by subjective economic status among general Japanese elderly people: a cross-sectional study with stratified random sampling. Issue 10 (7th October 2019) - Hidaka, Tomoo; Endo, Shota; Kasuga, Hideaki; Masuishi, Yusuke; Kakamu, Takeyasu; Kumagai, Tomohiro; Saito, Keiko; Abe, Kouichi; Fukushima, Tetsuhito
Abstract : Objectives: Pre-emptive conversations (PCs) about end-of-life (EOL) preferences are beneficial for both elderly people and their families to understand and share the preferences. However, the factors which promote/inhibit PCs have yet to be clarified. We therefore aimed to determine the factors related to having PCs with hypothesis that age, subjective economic status and subjective health status are associated with having PC experience. Design: A cross-sectional study administering a questionnaire and using stratified random sampling by gender and region. Setting: Residents aged 65 years or older who were not receiving nursing care as of 1 November 2016, were extracted from the Japanese long-term care insurance system registry in Koriyama City, Fukushima Prefecture, Japan. Participants: 1575 participants (717 males and 858 females). Outcome: Presence or absence of PC experience with family or friends (yes/no). Results: The mean age of the participants was 74.0 years. A multivariable logistic-regression analysis revealed that having PC experience was significantly associated with gender (OR=1.907; 95% CI=1.556 to 2.337; p<0.001), subjective economic status (OR=0.832; 95% CI=0.716 to 0.966; p=0.016) and subjective happiness (OR=0.926; 95% CI=0.880 to 0.973; p=0.003). Conclusions: Poor subjective economic status of elderly people may result in the absence of EOL conversation experience with their families and friends, hindering the elderly from sharing and understanding the EOL preferences. To promote PCs about EOL, gerontology and public health professionals should give special consideration to the subjective economic status of elderly people.